Foundational aspects of family-school partnership research - Sheridan, Susan M.; Moorman Kim, Elizabeth (Research on Family-School Partnerships ;, 2015)
This volume focuses on how family-school partnerships are conceptualized, defined, and operationalized as well as the research that is needed to advance these foundational issues. Each chapter integrates prevailing approaches into a research-based framework for supporting learning from pre-K through high school. The book incorporates structural and relational methods into the larger context of educational processes to promote research about collaboration and to improve the academic and behavioral development of students. Diverse theories and models of family-school alliances demonstrate approaches and interventions that are goal-directed and strengths-based, respectful and responsive. In addition, the book analyzes cognitive, behavioral, and interpersonal aspects of partnership and discusses different methods of assessing parental involvement and student outcomes. Included in the coverage are innovative, agenda-setting discussions on: Definitions and conceptual frameworks of family-school partnerships. Need-satisfying partnerships. Diverse parent perspectives and participation. Measurement of family-school partnership constructs over time. Foundational Aspects of Family-School Partnership Research is an essential resource for researchers, professionals, and graduate students in child and school psychology, educational policy and politics, family studies, developmental psychology, sociology of education, sociology, and anthropology.